New possibilities to determine wheat quality parameters by near-infrared spectroscopy - Kónya, Éva; Győri, Zoltán (Acta Agraria Debreceniensis, 2010)
Analyses and methods in wheat quality determination require more sample, time, work and cost, thatswhy flour quality control needs rapid, reliable tools. Near-infrared spectroscopy has many advantages, which make it suitable in quality control. NIR instruments need calibrations to their work. In our study we examined gluten content, falling number, valorigrpahic waterabsorption, alveographic P/L and W value of wheat samples. Modified partial least squares analyses on NIR spectra were developed for each property. The results show that we got such calibration modells, which are able to predict the properties (expect falling number) with enough accuracy.